Construction of Smart City Based on Open Government Data - Lei Gu; Yi Wang (Dianxin kexue)
Open government data（OGD）is a new evolving research field in smart city. As an important part of smart city, open government data allows new participation and collaboration in data reuse and utilization to create added value service. The key technologies of open government data include new information technologies such as metadata management, linked data, data visualization and social networks. Meanwhile, open government data propose additional infrastructure demands in smart city such as data center, network facilities and so on. In the open government data scheme, resources are utilized in a more intensive and efficient way. The state-of-the art of open government data in smart city was proposed. Moreover, the demand and technologies of open government data were introduced. Last but not least, the architecture design of open government data in smart city was illustrated.